Analisis Kandungan Karbon, Nitrogen Dan Jumlah Total Bakteri Pada Substrat Dasar Tambak Udang Vannamei (Litopenaeus vannamei) Pada Pertengahan Masa Tanam Di Desa Sanggalangit, Gerokgak, Buleleng, Bali. - Nadapdap, Nopita Sari; Perwira, Ima Yudha; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 3 No 1 (2020), 2020)
This study aims to determine the content of organic carbon, total nitrogen (TN), the total number of bacteria (TB) and the level of decomposition of organic matter in the bottom substrate of shrimp vannamei ponds (Litopenaeus vannamei) in Sanggalangit Village, Gerokgak District, Buleleng, Bali. Organic matter that is constantly accumulating on the pond bottom substrate can reduce the quality of the water. Data was collected in February-May 2019 using purposive sampling method with the number of ponds studied as many as 9 ponds. This research uses quantitative descriptive methods. Measurement of total nitrogen is done using the Indophenol method, organic carbon using the Walkley and Black method and total bacteria using the TPC (Total Plate Count) method. The results of this study obtained an average value of 29.34% organic carbon content, 1.15% total nitrogen and 15.2×10 6 total bacteria. The level of decomposition of organic matter in vannamei shrimp ponds (Litopenaeus vannamei) in Sanggalangit Village was included in the balanced category (C/N = 29.37). The measured C/N ratio indicates that the decomposition process of organic matter is going well so that the exchange of nutrients from the substrate to the pond water media is going well in supporting the pond productivity.